2017
DOI: 10.3389/fnins.2017.00235
|View full text |Cite
|
Sign up to set email alerts
|

Shared and Differential Retinal Responses against Optic Nerve Injury and Ocular Hypertension

Abstract: Glaucoma, one of the leading causes of blindness worldwide, affects primarily retinal ganglion cells (RGCs) and their axons. The pathophysiology of glaucoma is not fully understood, but it is currently believed that damage to RGC axons at the optic nerve head plays a major role. Rodent models to study glaucoma include those that mimic either ocular hypertension or optic nerve injury. Here we review the anatomical loss of the general population of RGCs (that express Brn3a; Brn3a+RGCs) and of the intrinsically p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
84
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 83 publications
(86 citation statements)
references
References 115 publications
(250 reference statements)
2
84
0
Order By: Relevance
“…19,[27][28][29][30][31] Retinal multiframe acquisitions of the whole retinas were acquired in a raster scan pattern using a 310 objective (Plan-Neofluar, 103/ 0.30; Zeiss Mikroskopie). Every single frame was focused manually before acquisition of the image.…”
Section: Retinal Image Analysis Quantification and Distribution Ofmentioning
confidence: 99%
“…19,[27][28][29][30][31] Retinal multiframe acquisitions of the whole retinas were acquired in a raster scan pattern using a 310 objective (Plan-Neofluar, 103/ 0.30; Zeiss Mikroskopie). Every single frame was focused manually before acquisition of the image.…”
Section: Retinal Image Analysis Quantification and Distribution Ofmentioning
confidence: 99%
“…23 In addition, ipRGCs show high resistance to optic nerve transection or crush, glutamate neurotoxicity, and acute ocular hypertension, but not to chronic ocular hypertension, suggesting that ipRGCs respond differently among injuries. [24][25][26] Glaucoma usually is associated with increased IOP, but a subset of glaucoma presents with statistically normal IOP, called normal tension glaucoma (NTG), suggesting the possibility that non-IOP-dependent factors may contribute to the disease progression. 27,28 We previously reported that loss of glutamate/aspartate transporter (GLAST) in mice leads to progressive RGC loss and optic nerve degeneration while maintaining normal IOP, demonstrating key pathologic features of NTG.…”
mentioning
confidence: 99%
“…It has been shown that non-image forming ipRGCs exhibited a preferential survival following injury compared to image forming RGCs. This fact was observed in different injury and disease models, demonstrating the resilience to damage of this subtype of RGCs [326]. ipRGCs have the ability to respond to light using the photopigment melanopsin, and they play a role in circadian rhythms and pupillary reflexes through their projections to the suprachiasmatic nucleus and the olivary pretectal nucleus [327].…”
Section: Different Types Of Rgcs and Their Susceptibility After Retinmentioning
confidence: 85%